Sistem Pengendalian Intern Pemerintah Dalam Penyelenggaraan Pemerintahan Oleh Pemerintah Kota Pekanbaru Tahun 2012 - ANINDITA, TRI ANUNG; ", ISRIL (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Issuance of Government Regulation No. 60 Year 2008 regarding the Government Internal Control System (SPIP) is expected to become an instrument of financial management to be more transparent and accountable. The quality of local government financial management is reflected in the opinion given by the Supreme Audit Agency (BPK) to Local Government Financial Reports (LKPD) each region. In 2012, LKPD of Pekanbaru only get a qualified opinion (WDP), there are several findings of the BPK, such as SPI-related issues and problems related to compliance with laws and regulations.This study aims to determine why SPIP no effect on the financial management of Pekanbaru City Government in 2012 . The method used in this study is qualitative, descriptive analysis techniques. For the success of this research will require people who know the problems in the field. The person is the Secretary of State Inspectorate Pekanbaru, Head of Government Affairs Government Supervisory Inspectorate Pekanbaru, Chief Financial Pekanbaru Revenue Office, Accounting and Finance Department head of Pekanbaru City Administration.Based on the findings in the field are compared with the theory SPIP PP. 60 in 2012 and Sarwoto Control Theory of effective controlling, The author concludes that no influential SPIP to Pekanbaru City Government financial management in 2012 is due to weak or not maximum SPIP was performed by Pemko Pekanbaru. This weakness is known of the existence of the SPIP elements that are not maximal implemented, such as the incomplete / absence of Standard Operating Procedure in work units, ineffective controlling, recommendations were not followed up, delays in financial reporting services, weak asset control and communication, lack of commitment of the government apparatus, leadership that is not conducive and human resources are weak. Besides being factors SPIP elements, there are also other factors such as there is no of Pekanbaru local regulations for the implementation of the SPIP and the problem of time it takes for SPIP be fully implemented.Keyword : SPIP, Controlling, LKPD